Kedudukan Hukum Pasien dalam Perjanjian Terapeutik di Indonesia - Franky Yusuf (Universitas Palangka Raya, 2024)
This article examines the legal position of patients in therapeutic agreements within Indonesia's healthcare system. The problem arises due to the imbalance of rights and obligations between healthcare providers and patients, which often leads to disputes. This study aims to analyze the legal standing of patients in therapeutic agreements, focusing on the principles of contract law and the obligations of healthcare providers. The research employs a normative juridical method, utilizing legal principles and case studies to investigate the regulatory framework governing therapeutic agreements. The findings reveal that despite existing legal protections, patients often face difficulties in exercising their rights due to lack of awareness and the unequal power dynamics in the patient-provider relationship. The study concludes that legal reforms are needed to strengthen patient protections and ensure a more balanced relationship between patients and healthcare providers. The implications of this research highlight the necessity of enhancing patient education and promoting greater accountability in the healthcare sector.